Donor‐Flexible Bis(pyridylidene amide) Ligands for Highly Efficient Ruthenium‐Catalyzed Olefin Oxidation. (25th March 2020) - Salzmann, Kevin; Segarra, Candela; Albrecht, Martin
Abstract: An exceptionally efficient ruthenium‐based catalyst for olefin oxidation has been designed by exploiting N, N ′‐bis(pyridylidene)oxalamide (bisPYA) as a donor‐flexible ligand. The dynamic donor ability of the bisPYA ligand, imparted by variable zwitterionic and neutral resonance structure contributions, paired with the redox activity of ruthenium provided catalytic activity for Lemieux–Johnson‐type oxidative cleavage of olefins to efficiently prepare ketones and aldehydes. The ruthenium bisPYA complex significantly outperforms state‐of‐the‐art systems and displays extraordinary catalytic activity in this oxidation, reaching turnover frequencies of 650 000 h −1 and turnover numbers of several millions. Abstract : Unstoppable : A ruthenium complex with a donor‐flexible bis(pyridylidene amide) (PYA) ligand catalyzes Lemieux‐type olefin oxidation at ppm‐level catalyst loadings with exceptionally high turnover frequencies (see picture). The ability of the PYA ligand to switch donor properties facilitates redox changes of the ruthenium center.